Association of junk food consumption with high blood pressure and obesity in Iranian children and adolescents: the CASPIAN-IV Study - Moloud Payab; Roya Kelishadi; Mostafa Qorbani; Mohammad Esmaeil Motlagh; Shirin Hasani Ranjbar; Gelayol Ardalan; Hoda Zahedi; Mohammad Chinian; Hamid Asayesh; Bagher Larijani; Ramin Heshmat (Elsevier, 2015)
OBJECTIVE: This study aimed to evaluate the association of junk food consumption with hypertension and obesity in a national sample of Iranian children and adolescents. METHODS: This nationwide study was conducted in 2011-2012 among 14,880 students, aged 6-18 years, selected by cluster sampling from 30 provinces. Weight, height, waist circumference (WC), hip circumference (HC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), as well as systolic and diastolic blood pressure (BP) were measured. Junk food was divided into four categories, including salty snacks, sweets, sweetened beverages, and fast food. Subjects reported how many times they had consumed each item (daily, weekly, and seldom). RESULTS: The intake of sweets was significantly associated with anthropometric indices and BP levels. Moreover, a significant association was found between fast food consumption, BP levels, and anthropometric indices (except for WHtR and WHR). Sweet beverages consumption was significantly associated with anthropometric indices; however, the consumption of salty snacks was only significantly associated with height, HC, and WHR. The risk of general obesity (OR: 0.75, 95% CI: 0.65-0.87) and abdominal obesity (OR: 0.81, 95% CI: 0.72-0.92) among participants who seldom consumed sweets was less than those who consumed daily. Also, the risk of general obesity (OR: 0.85, 95% CI: 0.74-0.97) among students that seldom consumed sweetened beverages was less than subjects who consumed them on a daily basis. CONCLUSION: It was found that junk food consumption increased the risk of both general and abdominal obesity; therefore, consumption of junk food should be reduced via restricting TV advertisements and increasing taxes on junk foods.